(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
Research objective of the current research aims to identify: The effect of using the (PQ4R) strategy on the cognitive achievement of the subject of methods of teaching physical education to female students. As for the hypothesis of the research, there are no statistically significant differences at the level (0.05) between the average scores of the students of the experimental group who study using the (PQ4R) strategy) and the mean scores of the students of the control group who study in the usual way. The limits of the research included a sample of fourth grade female students in the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University, for the academic year (2022-2023). Basics of teaching in physical education, authored by: Ismail Abd Zaid Ashour, and Emad Tohme Rady, 2016 AD. The researchers followed the experimental approach to achieve the goal of its research, as it is the most appropriate scientific method for the current research procedures. The current research community consists of fourth-grade students, Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University (2022-2023), whose number is 64 students distributed into five divisions (note that the halls consist of boys and girls) and the total number of students is 186 students, and the researchers selected a sample The current research, so the researchers randomly chose division (e) to be the experimental group that is taught with the (pq4r) strategy. Division (A) represents the control group, which is taught in the traditional way. The two researchers proceeded to conduct the sample equivalence to the cognitive achievement prepared by the researchers according to the scientific steps to build the cognitive achievement test. After that, an exploratory experiment was conducted, on the impact of which the scientific conditions for the cognitive achievement test were extracted. About the intelligence test, all these indicators were taken when building the achievement test, and then the cardiac test was conducted for the two groups, and educational units were prepared for the experimental group according to the strategy of Toms and Robinson (PQ4R). Scientific results based on the most important conclusions and recommendations, the most important of which is that teaching physical education methods using the Thomas and Robinson strategy (PQ4R) increases students’ cognitive achievement better than the traditional method. Using the strategy of Thomas and Robinson (PQ4R) in teaching the subject of methods of teaching physical education requires more time and effort from the school than the time and effort expended in the usual method. As for the recommendations of the research, it is the need to include in the courses of a school preparation program subject methods of teaching physical education in the colleges of education of strategies and modern methods of teaching such as meta-knowledge strategies, including Thomas and Robinson (PQ4R). The teaching process because of its impact on the cognitive achievement of students.